Revitalization of the Bukit Kunci Tourist Attraction Based on PLTB to Realize a Green Economy in Bangowan Village, Jiken District, Blora Regency: Revitalisasi Tempat Wisata Bukit Kunci Berbasis PLTB untuk Mewujudkan Green Economy Desa Bangowan Kecamatan Jiken Kabupaten Blora - Eva H. Herraprastanti; Hendri Suryanto; Teguh Yuwono; Retno Wahyusari; Daniswara Y. Alfreda; Rosalinda E. Putri (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
“Bukit Kunci” in Bangowan, Jiken, Blora Regency, is a hill tourist attraction developed by Pokdarwis “Bukit Kunci Asri” in 2019 and managed by BUMDes Bangowan Village. Partners' problems are an electrical power lack and the visitors number decrease. Currently the available electricity is not able to support facilities for lighting, water pumps and others equipment. Partners need additional power to increase the lights number in camping grounds, gazebos, toilets, add water pumps, cellphone, camera chargers and provide electricity at food stalls. With an income of 3.3 million/month from 600 visitors (before Covid-19), partners do not have enough funds to add electrical power. The solution offered is to build an Archimedes Turbine PLTB, due to hilly location with gusts of wind. The PLTB also be used as a new educational vehicle. Efforts to revitalize the Bukit Kunci tourist attraction based on PLTB as a step towards a sustainable green economy have been successfully implemented. The use of PLTB can produce additional sources of electricity to support the provision of electrical energy at the Bukit Kunci tourist location in addition to electricity from PLN. By increasing facilities at tourist locations, it has been proven that it can increase the number of visitors by 900 visitors from the initial 600 visitors (an increase of 50%) thus having an impact on increasing the income of the surrounding community.